Management of metastatic castration-resistant prostate cancer: A focus on radium-223: Opinions and suggestions from an expert multidisciplinary panel. (May 2017) - Baldari, Sergio; Boni, Giuseppe; Bortolus, Roberto; Caffo, Orazio; Conti, Giario; De Vincentis, Giuseppe; Monari, Fabio; Procopio, Giuseppe; Santini, Daniele; Seregni, Ettore; Valdagni, Riccardo
Highlights: Radium-223 improves survival, symptomatic skeletal events and quality of life. The radiopharmaceutical is best suited for patients with bone-predominant disease. This drug may also be given early in the course of the disease to improve outcome. Completion of six cycles of treatment is crucial in achieving effective dosing. Radium-223 is safe, well tolerated and does not interfere with subsequent therapies. Abstract: Radium-223, a calcium mimetic bone-seeking radionuclide that selectively targets bone metastases with alpha particles, is approved for the treatment of men with metastatic castration-resistant prostate cancer (mCRPC) and symptomatic bone metastases. In patients with mCRPC, treatment with radium-223 has been associated with survival benefit, regardless of prior docetaxel use, and also has a positive impact on symptomatic skeletal events and quality of life. Radium-223 is best suited for patients with symptomatic mCRPC and bone-predominant disease and no visceral metastases, and may lead to better outcomes when given early in the course of the disease. An expert multidisciplinary panel convened in Milan, Italy to review the current best-evidence literature on radium-223 and to convey their personal expertise with the use of radium-223 and identify possible strategies for best practice. This article summarizes the best available evidence for the use of radium-223, discusses the essential role of the multidisciplinary team in delivering effective treatment for mCRPC, clarifies pre- and post-treatment evaluation and monitoring, and outlines future scenarios for radium-223 in the treatment of men with MCRPC.